Strategi Digital Marketing Dengan Metode SEO (Search Engine Optimization) untuk UMKM di Desa Klambir 5 Kebun - Zulham, Zulham Sitorus; Andysah, Andysah Putera Utama Siahaan; Ibrahim, Ibrahim; Bambang, Bambang Sugito; Ayu, Ayu Ofta Sari; Anzas, Anzas Ibezato Zalukhu (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
The digital era has changed the way people carry out daily activities, including shopping. This provides an opportunity for Micro, Small and Medium Enterprises (UMKM ) to expand their market by utilizing digital marketing platforms. One digital marketing method that can be used by UMKM is Search Engine Optimization (SEO). SEO is a technique for optimizing a website so that it is easier for internet users to find via search engines. This research aims to analyze digital marketing strategies using the SEO method for UMKM in Klambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra. This research uses a qualitative descriptive method with data collection techniques in the form of literature study and in-depth interviews. The research results show that UMKM in Klambir Lima Kebun Village still do not understand the importance of SEO in their digital marketing strategy. Most UMKM only rely on social media to promote their products or services. However, social media cannot provide optimal results if it is not optimized with SEO. Based on the research results, it is recommended that UMKM in Klambir Lima Kebun Village implement a digital marketing strategy using the SEO method. This can be done by optimizing the website, content and social media. Keywords: Digital Marketing, SEO, UMKM, Klambir Lima Kebun Village